2021
DOI: 10.1088/1361-6595/abf31d
|View full text |Cite
|
Sign up to set email alerts
|

2D particle-in-cell simulations of geometrically asymmetric low-pressure capacitive RF plasmas driven by tailored voltage waveforms

Abstract: The effects of the simultaneous presence of two different types of plasma asymmetry, viz, geometric and electrical, on low-pressure capacitively coupled argon discharges are studied by 2D3V graphics-processing-unit-based particle-in-cell/Monte Carlo simulations. The geometric asymmetry originates from the different powered vs grounded electrode surface areas, while the electrical asymmetry is established by applying peaks/valleys and sawtooth-up/-down driving voltage waveforms. While in geometrically symmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 110 publications
0
29
0
1
Order By: Relevance
“…Thus, with the superposition effects of the increasing difference between the 125203-6 two electrode areas and the Gaussian waveform with a positive amplitude, the asymmetry of the discharge increases with the formation of a higher negative DC self bias. Wang et al [7] found from their particle simulation results that a thicker sheath would be formed at the powered electrode due to the strong negative DC self-bias, which can lead to fast sheath expansion and excitation of strong PSR oscillations. From our results, with the enhancement of the superposition of electrical and geometrical asymmetry, the absolute value of the negative DC self-bias voltage really becomes larger, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, with the superposition effects of the increasing difference between the 125203-6 two electrode areas and the Gaussian waveform with a positive amplitude, the asymmetry of the discharge increases with the formation of a higher negative DC self bias. Wang et al [7] found from their particle simulation results that a thicker sheath would be formed at the powered electrode due to the strong negative DC self-bias, which can lead to fast sheath expansion and excitation of strong PSR oscillations. From our results, with the enhancement of the superposition of electrical and geometrical asymmetry, the absolute value of the negative DC self-bias voltage really becomes larger, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 14(a), owing to the destructive superposition between the electrical asymmetry and geometrical asymmetry, the DC self bias is positive [7] and decreases as A d decreases, so the sheath becomes thinner and expands slowly, leading to the weakening of PSR oscillation and the decreasing of the resonance frequency. Figure 14(b) shows that with the decrease of the driving electrode area, the sheath capacitance lessens very slightly, but the bulk inductance increases a lot and gradually becomes the main reason for the resonance frequency decreasing, while the electrical asymmetry and geometrical asymmetry suppress each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…简单化学反应的氩气CCP放电, 一维(one dimensional, 1D)模拟大约需要1-2天 [17,58] , 柱坐标小 腔室(10 cm腔室半径, 2 cm电极间距)、低密度 (10 15 -10 16 m -3 )的串行二维(two dimensional, 2D) 模拟需要1-2周 [18] , 针对略大一些腔室结构(12 cm 腔室半径, 6.7 cm电极间距), 基于GPU的2D并 行PIC/MCC模拟同样需要10天左右 [19,59][3,59] 开发的基于GPU的2D PIC/MCC模型等.…”
Section: 以上条件的制约使得粒子模拟非常耗时 因此大部unclassified
“…The primary computational tool for these investigations has been the Particle-in-Cell/Monte Carlo Collisions (PIC/MCC) simulation. [55][56][57][58] This particle based approach is fully capable to capture kinetic effects, 59 therefore is well suited for the description of plasma sources operated at low pressures where non-local particle transport [60][61][62][63] appears. An analytical model 27 based on the voltage balance of the discharge has aided the understanding of the observations.…”
Section: Introductionmentioning
confidence: 99%